Analisis Diferensial dalam Pengambilan Keputusan Menjual Atau Memproses Lebih Lanjut - Rahmi, Mega; Septiani, Nazila; Rahmadani, Olivia; Putra, Yosep Eka (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study analyzes strategic decisions in managing a ground chili business, particularly in choosing between selling raw chilies or processing them into ground chili products. The research employs differential analysis to compare these two alternatives' revenue, costs, and contribution margins. Data were collected through interviews, direct observations, and documentation from UD Rahmad Usaha Hasil Bumi, a family-owned business operating for over two decades. The findings reveal that although the contribution margin per unit is higher for raw chili sales, the decision to further process chilies into ground chili products offers strategic advantages in product diversification and access to broader market opportunities. Break-even analysis was conducted to evaluate the business's financial feasibility, using contribution margin analysis and contribution margin ratio as key performance indicators. This study provides recommendations for business owners to prioritize product value addition as a critical factor in making business decisions.